Broadband infrared emissivity of Ag@SiO2 nanoparticles due to coupled transverse EM modes. Issue 15 (1st August 2022) - Rahman, Atta ur; Rehman, Fida; Shah, Abdul Hakim; Iqbal, M. Javid
Abstract: The extension of plasmonic spectra to the Mid-Infrared ( MIR ) spectral range (2 μm to 14 μm) of Silver coated Silica ( Ag@SiO 2 ) nanoparticles was discussed in this paper. Most of the previous findings in this regard, describe the intrinsic infrared response of individual Ag@SiO 2 particles or dimer and less explanation is available about the effect of electric field coupling over infrared radiation. This work provides detailed analysis about the contribution in the infrared response from the coupling of transverse EM (Electric-Magnetic) modes between the particles in the dimer. The simulated data also suggests a strong dependence of infrared radiation on the coupling of transverse EM which will facilitate the researchers in future to prepare the paint of randomly distributed Ag@SiO2 nanoparticles for passive radiative cooling. A smooth extra thin shell of Ag were deposited over SiO2 nanoparticles successfully, by employing wet chemical method. The morphology, qualitative and quantitative analysis were performed by using Transmission Electron spectroscopy ( TEM ) and Energy Dispersive X-ray Spectroscopy ( EDS ) respectively. The emissivity of the particles was measured with the Fourier Transform Infrared ( FTIR ) Spectrometer. The IR response of Ag@SiO 2 nanoparticles was simulated by employing the Finite Element Method ( FEM ) with the Microwave Studio in Computer Simulation Technology ( CST ) software. All the simulations and experimental results were found in agreement with slight difference between them. This slight difference has been explained in Modeling and Numerical analysis section.